Creation of a dedicated line team for critically ill patients with COVID-19: A multidisciplinary approach to maximize resource utilization during the COVID-19 pandemic. Issue 3 (May 2022) - Nawathe, Pooja; Wong, Robert; Pollock, Gabriel; Green, Jack; Kissen, Michael; Ng, Phillip; Cohen, Samuel; Barron, Joel; Robert, Stephen; Slingwine, Christy; Frank, Paul; Navab, Kaveh; et al.
Background: Pandemics create challenges for medical centers, which call for innovative adaptations to care for patients during the unusually high census, to distribute stress and work hours among providers, to reduce the likelihood of transmission to health care workers, and to maximize resource utilization. Methods: We describe a multidisciplinary vascular access team's development to improve frontline providers' workflow by placing central venous and arterial catheters. Herein we describe the development, organization, and processes resulting in the rapid formation and deployment of this team, reporting on notable clinical issues encountered, which might serve as a basis for future quality improvement and investigation. We describe a retrospective, single-center descriptive study in a large, quaternary academic medical center in a major city. The COVID-19 vascular access team included physicians with specialized experience in placing invasive catheters and whose usual clinical schedule had been lessened through deferment of elective cases. The target population included patients with confirmed or suspected COVID-19 in the medical ICU (MICU) needing invasive catheter placement. The line team placed all invasive catheters on patients in the MICU with suspected or confirmed COVID-19. Results and conclusions: Primary data collected were the number and type of catheters placed, time of team member exposure to potentially infected patients, and any complications over the first three weeks. Secondary outcomes pertained to workflow enhancement and quality improvement. 145 invasive catheters were placed on 67 patients. Of these 67 patients, 90% received arterial catheters, 64% central venous catheters, and 25% hemodialysis catheters. None of the central venous catheterizations or hemodialysis catheters were associated with early complications. Arterial line malfunction due to thrombosis was the most frequent complication. Division of labor through specialized expert procedural teams is feasible during a pandemic and offloads frontline providers while potentially conferring safety benefits.